Significantly enhanced cocatalyst-free H2 evolution from defect-engineered Brown TiO2. Issue 10 (15th May 2021) - Babu, S. Jagadeesh; Rao, V. Navakoteswara; Murthy, Dharmapura H.K.; Shastri, Mahesh; M, Murthy; Shetty, Manjunath; Raju, K.S. Anantha; Shivaramu, Prasanna D.; Kumar, C.S. Ananda; Shankar, M.V.; Rangappa, Dinesh
Abstract: TiO2 is the extensively investigated materials for various photocatalytic reforming and water splitting. Superior stability towards photo-corrosion, appropriate band energy levels driving most photocatalytic reactions, and low-cost production are promising features of TiO2 . However, a primary limitation with TiO2 is that it only absorbs ultraviolet light constituting less than 5% of the solar spectrum. In this work, we use a facile, low temperature, vacuum-free, and solution-route synthesis approach to rationally induce oxygen vacancy/Ti 3+ defects to reduce the bandgap of TiO2 to 2.0 eV (3.2 eV for pristine white TiO2 ) to form brown TiO2 with enhanced visible-light absorption. The mechanism of defect formation is systematically deduced from the detailed investigation through Raman spectroscopy, spin-sensitive technique, high-resolution microscopy, and surface analysis. The brown TiO2 yielded 8.1 mmol h −1 g −1 cat H2 evolution without any cocatalyst under natural sunlight, which is a factor two higher than pristine (white) TiO2 . To the best of our knowledge, the observed H2 evolution rate is the highest reported value under natural sunlight for any TiO2 -based photocatalyst. This work demonstrates the applicability of brown TiO2 to fabricate large-area photocatalyst panels for the cost-effective production of solar H2 .